2013
DOI: 10.1016/j.scitotenv.2013.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Study on the leaching of phthalates from polyethylene terephthalate bottles into mineral water

Abstract: Carbonated and non-carbonated mineral water samples bottled in 0.5-L, 1.5-L and 2.0-L polyethylene terephthalate (PET) containers belonging to three different water brands commercialized in Hungary were studied in order to determine their phthalate content by gas chromatography -mass spectrometry. Among the six investigated phthalates, diisobutyl phthalate, di-n-butyl-phthalate, benzyl-butyl phthalate and di(2-ethyl-hexyl) phthalate (DEHP) were determined in non-carbonated samples as follows: 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
4
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 31 publications
6
72
4
2
Order By: Relevance
“…When examining the levels of DEHP in the bottled water over time, some studies report increasing concentrations (Casajuana and Lacorte 2003;Guart et al 2014;Keresztes et al 2013;Leivadara et al 2008) and others report constant or even decreasing levels of DEHP (Al-Saleh et al 2011;Diana and Dimitra 2011;Guart et al 2014;Keresztes et al 2013). A decrease of DEHP concentration would mean that some kind of breakdown had occurred, which seems unlikely.…”
Section: Bottled Watermentioning
confidence: 99%
See 1 more Smart Citation
“…When examining the levels of DEHP in the bottled water over time, some studies report increasing concentrations (Casajuana and Lacorte 2003;Guart et al 2014;Keresztes et al 2013;Leivadara et al 2008) and others report constant or even decreasing levels of DEHP (Al-Saleh et al 2011;Diana and Dimitra 2011;Guart et al 2014;Keresztes et al 2013). A decrease of DEHP concentration would mean that some kind of breakdown had occurred, which seems unlikely.…”
Section: Bottled Watermentioning
confidence: 99%
“…A decrease of DEHP concentration would mean that some kind of breakdown had occurred, which seems unlikely. Even within individual studies, both increases and decreases of DEHP concentration have been reported over time (Guart et al 2014;Keresztes et al 2013).…”
Section: Bottled Watermentioning
confidence: 99%
“…≥10 and ≤3. DEP and DBP are usually degraded more than 20 % by hydrolysis under acidic and high temperature conditions (25). However, in the case of DEHP, the effect of hydrolysis is negligible due to spatial crowding around hydrolysis site.…”
Section: Resultsmentioning
confidence: 99%
“…Single use plastic bottles are made of Polyethylene Terephthalate (PET), which make products softer and more flexible. Phthalates have been linked to cancer (Keresztes et al 2013). Single use bottles also contain antimony, this can cause negative health effects such as nausea, vomiting, and diarrhoea when exposure exceeds the tolerability levels for relatively short periods (Rungchang et al 2013).…”
Section: Case 1 Water Bottlesmentioning
confidence: 99%